Analysis of Resident Satisfaction Evaluation at St. Titus Brandsma Dormitory Using Importance Performance Analysis Method - Caleg Sadrak Sinaga; Desinta Purba (SEAN Institute, 2026)
St. Titus Brandsma Dormitory was built to provide temporary housing for male students of Santo Thomas Catholic University Medan. To date, the evaluation is determined by the priest at the end of the semester through a collective discussion in the dormitory hall. This study aims to measure the level of satisfaction of dormitory residents and determine service attributes that are priority for improvement using the Importance Performance Analysis (IPA) method. Research data were obtained through distributing questionnaires to dormitory residents using a Likert scale that measures the level of importance and performance. The results of the analysis show that most residents are in the satisfied category with the facilities and services provided. The study results on dormitory resident satisfaction revealed that 33.93% of respondents felt highly satisfied, whereas 42.86% indicated that they were satisfied. In addition, 19.64% of the respondents felt fairly satisfied, whereas 1.79% expressed dissatisfaction and another 1.79% indicated that they were very dissatisfied. The results of the Importance Performance Analysis also showed that the availability of a stable Wi-Fi signal across the dormitory area was categorized in Quadrant I, meaning it became the main priority for improvement. Therefore, enhancing the Wi-Fi service should be addressed immediately to increase resident satisfaction.